Industrial Geotourism and Geoeducation Potential of SE Türkiye: A Case Study of the Petroleum Industry in the Adıyaman Region - Mulayim, Oguz; Koroglu, Fatih; Alkac, Onur (Springer Heidelberg, 2024)
Adiyaman (SE Turkiye) has a spectacular geological record and high-quality outcrops of petroleum systems. Turkiye is an important resource area for the petroleum industry. The petroleum sector impacts development and provides opportunities for geotourism and geoeducation. Most of these sedimentary and tectonically related geological records form sites relevant to petroleum geology that provide favourable conditions for geoeducational activities with special emphasis on the framework of hydrocarbon exploration models in fieldwork. These georoutes should be popularised for those who work in the petroleum industry, colleagues who are not yet familiar with them and are interested in these concepts, and even for students who are leaning in this direction. This study is about geotourism at sites that are related to the petroleum industry, which could serve as pioneering examples in SE Turkiye and their potential as industrial geotourism resources. In addition, all of these sites are ideal for conducting various geoeducational and geotourism activities for the purposes of geoconservation. Due to the uniqueness of this study, the industrial geoheritage of Adiyaman will become more accessible for scientific research and play an important role in geoeducation and as a potential geotourism resource.
Keywords: Industrial geotourism; Geoeducation; Geoconservation; Georoute